Keynes : Useful Economics for the World Economy - Temin, Peter; Vines, David (Book collections on Project MUSE., 2014)
As the global economic crisis continues to cause damage, some policy makers have called for a more Keynesian approach to current economic problems. In this book, economists Peter Temin and David Vines provide an accessible introduction to Keynesian ideas that connects Keynes's insights to today's global economy and offers readers a way to understand current policy debates. They survey economic thinking before Keynes and explain how difficult it was for Keynes to escape from conventional wisdom. They set out the Keynesian analysis of a closed economy and expand the analysis to the international economy, using a few simple graphs to present Keynes's formal analyses in an accessible way. They discuss problems of today's world economy, showcasing the usefulness of a simple Keynesian approach to current economic policy choices. Keynesian ideas, they argue, can lay the basis for a return to economic growth. --